2020
DOI: 10.7150/jca.38274
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a robust multigene signature as an aid to predict early relapse in stage I-III clear cell and papillary renal cell cancer

Abstract: Background and objectives:Multi-gene signature can be used as prognostic indicator in many types of cancer, but the association with early-relapse in patients with stage I-III clear cell and papillary renal cell cancer (RCC) is unknown. We aim to establish a mRNAs signature for improving prediction of early-relapse in patients with stage I-III clear cell and papillary RCC. Methods: The data of 610 patients with stage I-III RCC from The Cancer Genome Atlas (TCGA) and 270 patients from Fudan University Shanghai … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Some researchers have developed several signatures on the prognosis of PRCC at the molecular level, including mRNA, lncRNA, alternative splicing, mutation and etc., ( Cao et al, 2020 ; Duan and Zhang, 2019 ; Zhang C. et al, 2019 ; Zuo et al, 2018 ). Previous study reported a five-gene signature to predict overall survival of patients with PRCC ( Gao et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers have developed several signatures on the prognosis of PRCC at the molecular level, including mRNA, lncRNA, alternative splicing, mutation and etc., ( Cao et al, 2020 ; Duan and Zhang, 2019 ; Zhang C. et al, 2019 ; Zuo et al, 2018 ). Previous study reported a five-gene signature to predict overall survival of patients with PRCC ( Gao et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is similar to what we have seen in our other studies using the TCGA gene expression and methylation data. 92,93 Strengths of our study include a multistage design that consisted of two discovery independent discovery datasets and a validation dataset; the use of NanoString platform that allows for accurate and reproducible measurement of RNA from FFPE samples; selection of candidate genes based on a thorough literature search [9][10][11][12][13][14][15][16][17][18][19] ; and validation of the role of identified genes previously implicated in ccRCC and are potential targets for novel cancer therapies. Indeed, inhibitors of some of these genes are already in early phase I trials.…”
Section: Discussionmentioning
confidence: 99%
“…Candidate ccRCC-related genes were selected based on previous published literature., [9][10][11][12][13][14][15][16][17][18][19] including our review article 19 and pathways described in the Cancer Genome Anatomy project. A total of 388 candidate genes were evaluated in the discovery sets.…”
Section: Gene Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some researchers have developed several signatures on the prognosis of PRCC at the molecular level, including mRNA, lncRNA, alternative splicing, mutation and etc. [22][23][24][25]. However, these signatures have not yet reached a robust high accuracy rate, and have not considered the important impact of tumor immunology on the prognosis and treatment of PRCC.…”
Section: Discussionmentioning
confidence: 99%